Environmental Problems: An Analysis of Students’ Perceptions Towards Selective Waste Collection - Gherheş, Vasile; Fărcaşiu, Marcela Alina; Para, Iulia (Frontiers in Psychology, 2022)
The reduction, reuse, collection and recovery of recyclable materials are sustainable behaviors and people’s awareness of them plays an important role in implementing strategies and policies in this field. The quantitative analysis performed on a group of 816 students of Politehnica University of Timisoara, aimed at finding answers to important environmental concerns and observing the students’ behaviors of reuse and selective collection of the waste resulted from plastic containers, paper, aluminum, batteries, iron packaging waste, electronic equipment, used cooking oil and printer toner. The research has shown that `increased amounts of waste` is among the first three concerns Romania has to deal with, besides `air pollution` and `deforestation`. Moreover, the study highlights the existence of the behavior towards the selective waste collection among students, although there are some areas (e.g. selectively collecting used cooking oil or printer toner, their level of knowledge regarding the color code for the recycling bins, etc.) that students still need to be familiarized with through different campaigns, trainings, courses, etc. The results can be used in the development of institutional strategies or of strategic documents targeting environmental protection and sustainable development. The blockchain technology could be a solution in the waste management field, aiming to fight climate change for a more sustainable development, but also to comply with the European Union regulations.